(untitled) (Brazilian Journal of Health Research, 2024)
Introduction: Roux-en-Y gastric bypass (RYGB) by laparoscopy (LRYGB) has better results than open surgery, but they have not been compared in Brazilian Public Health System and is not funded by governmental entities. Objectives: to assess safety and efficacy of laparoscopic RYGB (LRYGB) in Brazilian Public Health System (SUS) and to compare with open RYGB (ORYGB). Methods: single-center retrospective cohort study, with 106 consecutive patients who underwent primary RYGB: 34 laparoscopic RYGB and 72 open RYGB. Antropometric data, incidence of complications and readmissions were analyzed. Results: There were 82,1% female, mean age of 43,01 years old, mean body mass index (BMI)=45,05kg/m² and mean follow-up of 17,57 months. BMI was lower in LRYGB group (42,31 x 46,35kg/m²; p=0,003), that also had higher preoperative weight loss (6,94 x 4,12%; p=0,016), lower mean age (36,53 x 46,07 anos; p=0,000) and shorter anesthesia time (217,93 x 274,15min, p<0,00). Postoperatively, LRYGB group’s mean BMI=29,46 vs. 32,22kg/m² of ORYGB (p=0,014), and excess BMI loss (EBMIL) is 81,01% vs. 68,20% of ORYGB (p=0,023). ORYGB group had more complications than LRYGB group (54,2% x 38,2%, p>0,05). There were more Clavien-Dindo ≥ III complications in ORYGB group (48,7% x 15,4%, p>0,0,34). Readmissions were more frequent in ORYGB group (9,7% x 2,9%), that also had higher incidences of incisional hernia (9,7%), internal hernia (2,8%) and wound complications (12,5%), all of these parameters were null in LRYGB group (p>0,05). Conclusion: LRYGB in SUS is safe and effective. LRYGB patients present lower severe complications, mortality, readmissions and reoperations rates.